A Retrospective Assessment of The Safety Profile of Pioglitazone in T2dm Patients - Saini, Aryendu Kumar; Verma, Sunil; Bansode, Himanshu; Yadav, Vishal; Kumar, Upendra; Chaubey, Byomnath; Kushwaha, Pratima (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Pioglitazone is a drug that belongs to the category of thiazolidinedione (TZD) and is used for its hypoglycemic activity that is very-well associated with some serious adverse drug reactions (ADR). Previous studies have dealt with country-specific pharmacovigilance databases to assess the ADR profile of pioglitazone but none of them utilized a scholarly literature database. Objective: This study was conducted to assess the safety profile of pioglitazone in terms of expectedness, causality, and the seriousness of ADR by using a literature database. Methods: The published literature cases of pioglitazone-induced ADR from the PubMed database (between 1993 and 2020) were retrieved by using Medical Subject Headings (MeSH) terms.Only the valid cases (as per the ICH validity criteria) were analyzed. Following this, valid cases were further assessed for the expectedness of ADR by using the "Summary of Product Characteristics" document of Takeda Pharmaceuticals UK Ltd. Seriousness criteria of WHO for ADR were used for assessing the seriousness of ADR while the Naranjo’s scale was used for causality assessment. Results: A total of 871 results were found of which only 26 valid ICSRs cases were found. Of the total 168 ADRs, a total of 131 (77.97%) and 37 (22.02%) unexpected and expected ADRs were found. Only two of the events were found to be non-serious and they were Iatrogenic lipomatosis and Angioneurotic edema. 1 (32.5 %), 24 (77.4 %), 6 (19.35 %) reactions were serious due to death, important medical event, and hospitalization, respectively. There were, in total, 7 (27 %) and 19 (74 %) cases that belonged to a possible and probable category, respectively. Conclusion: It is worth mentioning that pioglitazone is associated with the risk of heart failure and edema besides causing bladder cancer. The patient should be evaluated for the possible adverse effects of proper monitoring and follow-ups.